CircTRRAP Knockdown Has Cardioprotective Function in Cardiomyocytes via the Signal Regulation of miR-370-3p/PAWR Axis - Yuan Zhang; Zhenggong Li; Jiao Wang; Hao Chen; Rui He; Hongkun Wu (Cardiovascular Therapeutics)
Background. Circular RNA Transformation/Transcription Domain Associated Protein (circTRRAP, hsa_circ_0081241) was abnormally upregulated in acute myocardial infarction (AMI) patients. However, its biological role and functional mechanism in AMI remain to be researched. Methods. Human cardiomyocyte AC16 was exposed to hypoxia to induce cell injury. Cell viability was detected through Cell Counting Kit-8. CircTRRAP, microRNA-370-3p (miR-370-3p), and Pro-Apoptotic WT1 Regulator (PAWR) levels were assayed by reverse transcription-quantitative polymerase chain reaction. Cell proliferation analysis was performed via 5-ethynyl-2′-deoxyuridine (EdU) assay. Cell apoptosis was assessed using flow cytometry and caspase-3 activity assay. The protein levels were measured through western blot. Enzyme-linked immunosorbent assay was used to examine the release of inflammatory cytokines. Oxidative stress was assessed by the commercial kits. Dual-luciferase reporter assay, RNA immunoprecipitation, and RNA pull-down assays were performed for the validation of target interaction. Results. CircTRRAP was highly expressed following hypoxia treatment in AC16 cells. Downregulation of circTRRAP promoted cell growth but inhibited apoptosis, inflammation, and oxidative stress in hypoxic cells. CircTRRAP could target miR-370-3p, and the regulatory effects of circTRRAP on the hypoxic cells were associated with the sponge function of miR-370-3p. PAWR served as the target for miR-370-3p, and it was regulated by circTRRAP/miR-370-3p axis. The protective role of miR-370-3p was achieved by downregulating the PAWR expression in hypoxia-treated AC16 cells. Conclusion. These findings demonstrated that silence of circTRRAP exerted the protection against the hypoxia-induced damages in cardiomyocytes through regulating the miR-370-3p and PAWR levels.